PELATIHAN HOLD RELAX DAN TERAPI MANIPULASI LEBIH MENINGKATKAN AKTIVITAS FUNGSIONAL DARIPADA PELATIHAN CONTRACT RELAX DAN TERAPI MANIPULASI PADA PENDERITA FROZEN SHOULDER - Lalu Suprawesta (Universitas Pendidikan Mandalika, 2017)
Frozen shoulder resulted in a complaint when performing movements that affect the ability of the shoulder joint in performing of daily functional activities. Some methods such as hold-relax and contract relax training on PNF method sometimes conducted alternately or simultaneously, often used to improve ROM and maintain the quality of the joints. Manipulation therapy is widely used by physiotherapists to improve the mobility of joints that have limitations. This study aims to prove the effectiveness of treatment in patients with frozen shoulder in order to improve functional activities by comparing the hold relax training and manipulation therapy and contract relax training and manipulation therapy.This study uses a true experimental with pre-test and post-test two group design. This study was conducted in Physiotherapy Plus clinic Denpasar in March until April 2015. These study samples included 18 people were divided into two treatment groups. The treatment group I received treatment hold relax training and manipulation therapy followed by 9 samples and the treatment group II received treatment contract relax training and manipulation therapy followed by 9 samples. Measuring instruments used is SPADI index to determine the percentage of SPADI value to know limitations of functional activity among patients with frozen shoulder, which is measured before and after getting treatment.The results of comparative tests carried out tests of Independent sample t test on the mean±SD of the percentage of SPADI value. The mean±SD of the percentage of SPADI value on both treatment group before treatment were no different. Hypothesis testing results indicate a significant difference to the improvement of functional activity limitations on the mean of the percentage of SPADI value after the treatment group I 31,19±9,30 and after the treatment group II 46,83±8,24 with p=0.002. In this study, it is known that the hold relax training and manipulation therapy more increase the functional activity rather than the contract relax training and manipulation therapy. Further studies of this training method is still needed to determine the dose of exercise and modification program in order to help people more quickly with frozen shoulder in improving functional activities